Bird Communities in a Changing World: The Role of Interspecific Competition - Alban Guillaumet; Ivory Jordan Russell (Diversity, 2022)
Significant changes in the environment have the potential to affect bird species abundance and distribution, both directly, through a modification of the landscape, habitats, and climate, and indirectly, through a modification of biotic interactions such as competitive interactions. Predicting and mitigating the consequences of global change thus requires not only a sound understanding of the role played by biotic interactions in current ecosystems, but also the recognition and study of the complex and intricate effects that result from the perturbation of these ecosystems. In this review, we emphasize the role of interspecific competition in bird communities by focusing on three main predictions derived from theoretical and empirical considerations. We provide numerous examples of population decline and displacement that appeared to be, at least in part, driven by competition, and were amplified by environmental changes associated with human activities. Beyond a shift in relative species abundance, we show that interspecific competition may have a negative impact on species richness, ecosystem services, and endangered species. Despite these findings, we argue that, in general, the role played by interspecific competition in current communities remains poorly understood due to methodological issues and the complexity of natural communities. Predicting the consequences of global change in these communities is further complicated by uncertainty regarding future environmental conditions and the speed and efficacy of plastic and evolutionary responses to fast-changing environments. Possible directions of future research are highlighted.